Fiscal policy, growth and poverty reduction in Uganda - Steve Kayizzi-Mugerwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
After more than a decade of economic decline and civil war, Uganda was able to return to economic growth thanks to the policies pursued by Museveni's National Resistance Movement which elicited considerable donor support. They include macroeconomic reforms, public sector restructuring, privatisation and decentralization, all with emphasis on poverty reduction. The government recognises that fiscal policy is the key to success and much effort has, in the past decade, gone towards fiscal reforms and the improvement of institutional capacities. Still, in a country with limited finances and a thin tax base the competition for resources has been stiff. While the government has been able to embark on initiatives such as universal primary education, thanks to an improved revenue base and donor support, the decentralization drive is hindered by serious fiscal constraints at the local level.
Keywords: O23; H30; O55; 330; fiscal policy; growth; poverty reduction; Uganda; Africa; Finanzpolitik; Dezentralisierung; Privatwirtschaft; Entwicklungshilfe; Armut; Uganda